Implementation of a pharmacogenetic panel‐based test for pharmacotherapy‐based supportive care in an adult oncology clinic - Emily J. Cicali; Elizabeth Eddy; Yan Gong; Amanda L. Elchynski; Kim Pena del Aguila; Tala Basha; Karen C. Daily; Lauren Dickson; Steven Fischer; Erin Hastings‐Monari; Dennie Jones Jr; Brian H. Ramnaraign; et al. (Wiley, 2024)
Abstract The University of Florida Health conducted a pragmatic implementation of a pharmacogenetics (PGx) panel‐based test to guide medications used for supportive care prescribed to patients undergoing chemotherapy. The implementation was in the context of a pragmatic clinical trial for patients with non‐hematologic cancers being treated with chemotherapy. Patients were randomized to either the intervention arm or control arm and received PGx testing immediately or at the end of the study, respectively. Patients completed the MD Anderson Symptom Inventory (MDASI) to assess quality of life (QoL). A total of 150 patients received PGx testing and enrolled in the study. Clinical decision support and implementation infrastructure were developed. While the study was originally planned for 500 patients, we were underpowered in our sample of 150 patients to test differences in the patient‐reported MDASI scores. We did observed a high completion rate (92%) of the questionnaires; however, there were few medication changes (n = 6 in the intervention arm) based on PGx test results. Despite this, we learned several lessons through this pragmatic implementation of a PGx panel‐based test in an outpatient oncology setting. Most notably, patients were less willing to undergo PGx testing if the cost of the test exceeded $100. In addition, to enhance PGx implementation success, reoccurring provider education is necessary, clinical decision support needs to appear in a more conducive way to fit in with oncologists' workflow, and PGx test results need to be available earlier in treatment planning.